Model-guided development of pharmacokinetic/pharmacodynamic cut-offs and evaluation of sitafloxacin dosing regimens against target pathogens - Wu, Hailan; Li, Yi; Li, Xin; Fan, Yaxin; Guo, Beining; Liu, Xiaofen; Li, Wanzhen; Chen, Mengting; Chen, Yan; Zhang, Jing (Frontiers in Pharmacology, 2025)
IntroductionThe establishment of clinical breakpoints for antimicrobial drug is crucial for guiding appropriate therapeutic interventions. This study aims to identify the pharmacokinetic/pharmacodynamic (PK/PD) cut-offs for using sitafloxacin against target pathogens to support clinical breakpoint establishment for antimicrobial drug sensitivity testing.MethodsA population PK (PopPK) model was built (342 subjects) to calculate the dosing-regimen-dependent (50 mg q12 h, 100 mg q24 h and 100 mg q12 h) PK parameters of sitafloxacin-infected patients, which were combined with in vitro PD data and PK/PD target data. The probabilities of attainment (PTAs) and cumulative fraction of response (CFR) values for different sitafloxacin dosing regimens against Streptococcus pneumoniae, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa were calculated via Monte Carlo simulation.ResultsPopPK modelling revealed that the PK profile of sitafloxacin was consistent with a two-compartment model with first-order elimination. Creatinine clearance affected total clearance, bodyweight and age affected the central ventricular apparent volume of distribution, and food affected the sitafloxacin absorption rate. On the basis of the animal infection model target (fAUC24h/MIC = 11.56), the anti-Streptococcus pneumoniae sitafloxacin dosing regimen PTAs were >95% (MIC ≤ 0.06, ≤0.06, ≤0.125 mg/L; CFRs = 98.2∼99.3%). With a clinical study target of fAUC24h/MIC ≥ 30, the anti-Streptococcus pneumoniae dosing regimen PTAs were >95% (MIC ≤ 0.03, ≤0.03, ≤0.06 mg/L; CFRs = 89.2∼97.3%). For the other four strains, the dosing-regimen-dependent sitafloxacin PK/PD cut-offs were 0.06, 0.06 and 0.125 mg/L, respectively (CFRs = 56.3∼76.9%).DiscussionOur findings suggest that sitafloxacin PK/PD cut-offs of S ≤ 0.06 mg/L and R > 0.125 mg/L should be used against these five strains and that the sitafloxacin dosing regimens (50 mg q12 h, 100 mg q24 h and 100 mg q12 h) have the expected efficacy against Streptococcus pneumoniae-related infections, but the efficacy against Pseudomonas aeruginosa-associated infections needs to be verified in clinical practice.